The lecturer’s toolkit : - Race, Philip (Kogan Page, 2001)
"The Lecturer's Toolkit" was first published as a photocopyable ring-bound resource and was an immediate success for all those in higher education seeking to develop learning and teaching skills. Now fully revised, the second edition is available both as an A4 ring-binder and as a paperback edition for the first time. This new edition will be equally valued by individuals and by staff-developers for group work.